"Men's health – a little in the shadow": a formative evaluation of medical curriculum enhancement with men's health teaching and learning. Issue 1 (December 2015) - Holden, Carol; Collins, Veronica; Anderson, Christopher J.; Pomeroy, Sylvia; Turner, Richard; Canny, Benedict; Yeap, Bu; Wittert, Gary; McLachlan, Rob
Abstract Background Enhancing a medical school curriculum with new men's health teaching and learning requires an understanding of the local capacity and the facilitators and barriers to implementing new content, and an approach that accommodates the systemic and cultural differences between medical schools. Methods A formative evaluation was undertaken to determine the perspectives of key informants (academics, curriculum developers) from four Australian medical schools about the strategies needed to enhance their curriculum with men's health teaching and learning. Through semi-structured questioning with 17 key informants, interviewees also described the contextual barriers and facilitators to incorporating new topic areas into existing curriculum. Interviews were recorded with consent, transcribed verbatim, and analysed by two researchers to identify key themes. Results Interviewees were enthusiastic about incorporating men's health content through a men's health curriculum framework but highlighted the need for systems to assist in identifying gaps in their current curriculum where the men's health topics could be integrated. The student experience was identified as a key driver for men's health teaching and learning. Furthermore, core men's health clinical outcomes needed to be defined and topic areas vertically integrated across the curricula. This would ensure that students were appropriately equipped with the skills and knowledge for subsequent clinical practice in a range of geographical settings. Interviewees consistently suggested that the best implementation strategy is to have someone 'on the ground' to work directly with medical school staff and champion the men's health discipline. Providing mechanisms for sharing knowledge and resources across medical schools was highlighted to facilitate implementation, particularly for those medical schools with limited men's health teaching resources. Conclusions Despite the unanimous support for men's health teaching and learning, the evaluation highlighted that the student experience must be recognised as paramount when integrating new topic areas into an already packed curriculum. A community of practice, where medical schools share relevant resources and knowledge, could help to ensure a commonality of student experience with respect to men's health learning in medical schools across different geographical settings and with different levels of resourcing. Such an approach could also be adapted to other areas of curriculum enhancement.